Physicochemical properties and in vitro mineralization of porous polymethylmethacrylate cement loaded with calcium phosphate particles. Issue 3 (21st June 2014) - Sa, Yue; Yang, Fang; Leeuwenburgh, Sander C. G.; Wolke, Joop G. C.; Ye, Guang; de Wijn, Joost R.; Jansen, John A.; Wang, Yining
Abstract: The main goal of this study was to evaluate the effects of incorporation of calcium phosphate (CaP) particles on the physicochemical properties and mineralization capacity of cements in vitro . Herein, two different types of CaP particles were loaded into polymethylmethacrylate (PMMA) cements exhibiting an interconnected porosity created by mixing with carboxymethylcellulose. The incorporation of CaP particles did not influence the maximum polymerization temperature of the porous PMMA, but reduced the porosity and the average pore size. Small CaP particles formed agglomerations within the PMMA pores, whereas big CaP particles were partially embedded in the PMMA matrix and partially exposed to the pores. Both types of CaP particles enhanced the mineralization capacity of PMMA cement without compromising their mechanical properties. The data presented herein suggest that porous PMMA/CaP cements hold strong promise for surgical application in bone reconstruction. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 548–555, 2015.